Princess Justina Albertina : a cautionary tale - Davidson, Ellen Dee, 1954- (Charlesbridge, 2007)
A spoiled, demanding young princess who sends her nanny to the far corners of the world in search of the perfect pet finally gets exactly what she deserves.